Perhitungan Volume Bahan Bakar Kapal Perintis KM Sabuk Nusantara 71 Dengan Metode Simson I dan Autocad - Langgeng, Diana; Saputra, Dimas Adi (Marine Science and Technology Journal, 2021)
Calculating the volume of the ship is irregular using the Simson method. The simson measurement is to first calculate the volume of a certain room that is irregular, then divide the room into several parts. Then the calculation results of the Simson I method, autocad are compared which is the closest to knowing the tank volume of the model. From the results of data analysis it can be determined that simson 184.068267 m3, autocad 176.183925 m3.